Comparable actions of omalizumab on mast cells and basophils. Issue 1 (January 2016) - Serrano‐Candelas, E.; Martinez‐Aranguren, R.; Valero, A.; Bartra, J.; Gastaminza, G.; Goikoetxea, M. J.; Martín, M.; Ferrer, M.
Summary: Background: Omalizumab (OmAb) has recently been approved for the treatment of diseases other than allergic asthma, including chronic urticaria. The exploration of the use of OmAb in chronic urticaria was based on the presence of IgE autoantibodies against autoantigens such as anti‐IgE, anti‐FcεRI, and IgE antibodies against thyroid peroxidase in certain patients with chronic urticaria. OmAb recognizes and sequesters free IgE to prevent its interaction with FcεRI. However, OmAb is equally and rapidly effective against autoimmune and non‐autoimmune urticaria, suggesting the possible involvement of additional mechanisms of IgE. Objectives: We sought to investigate the in vitro mechanism of action of OmAb in mast cells and basophils. Methods: Both LAD2 human mast cell line, previously sensitized with IgE, and ex vivo basophils were incubated with OmAb at different doses, analysing its effect on IgE‐dependent events (e.g., degranulation, phosphorylation‐mediated signalling, and eicosanoid release). Results: We found that OmAb dissociates pre‐bound IgE from mast cells and basophils, resulting in a reduction of proximal phosphorylation‐mediated signalling events (Syk, PLCγ, and LAT) and in a decrease in degranulation and leukotriene synthesis. Conclusion: Our data prove the existence of common mechanisms of action of OmAb in mast cells and basophils that would explain its effectiveness and rapid effect in chronic urticaria and provide a basis for its use in other diseases mediated by these cells.